Some Issues of Legislation of the Republic of Armenia in the Field of Water Resource Vulnerability and Adaptation in the Context of Climate Change - Geghamyan, O. (Bulletin of Yerevan University C: Jurisprudence, 2020)
Legal norms related to water resource adaptation in the context of climate change were assessed and analyzed within the framework of this article, paying an emphasis on some gaps and shortcomings of the water legislation of the RA. The international legislation and obligations of the Republic of Armenia, existing legislative obstacles in this area are presented in detail, as well as proposals for resolving these issues.
Keywords: water resource vulnerability and adaptation in the context of climate change, water use rates, biological monitoring, water basin management plan